2022
DOI: 10.1186/s12885-022-09763-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the potential mechanism of emetine against coronavirus disease 2019 combined with lung adenocarcinoma: bioinformatics and molecular simulation analyses

Abstract: Background Patients with lung adenocarcinoma (LUAD) may be more predisposed to coronavirus disease 2019 (COVID-19) and have a poorer prognosis. Currently, there is still a lack of effective anti-LUAD/COVID-19 drugs. Thus, this study aimed to screen for an effective anti-LUAD/COVID-19 drug and explore the potential mechanisms. Methods Firstly, we performed differentially expressed gene (DEG) analysis on LUAD transcriptome profiling data in The Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that CCNA2 can be a key target for the treatment of lung adenocarcinoma, and abnormal expression of CCNA2 plays a critical role in the development of lung adenocarcinoma. [ 37 ] In addition, it has been shown that CCNA2 has a protective effect on innate immune responses and helps to reduce pathogen-induced inflammation and apoptosis, while CCNA2 is also critical for the regulation of immune-related gene expression. [ 38 ] CCNB1, a member of the G2/mitotic-specific cyclin B1 family, controls the transition from G2 to M phase, is expressed in G2 phase and degraded in M phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CCNA2 can be a key target for the treatment of lung adenocarcinoma, and abnormal expression of CCNA2 plays a critical role in the development of lung adenocarcinoma. [ 37 ] In addition, it has been shown that CCNA2 has a protective effect on innate immune responses and helps to reduce pathogen-induced inflammation and apoptosis, while CCNA2 is also critical for the regulation of immune-related gene expression. [ 38 ] CCNB1, a member of the G2/mitotic-specific cyclin B1 family, controls the transition from G2 to M phase, is expressed in G2 phase and degraded in M phase.…”
Section: Discussionmentioning
confidence: 99%
“…DPP4 inhibitors are commonly used to treat type 2 diabetes. Interestingly, many studies have shown that some DPP4 inhibitors (such as: selegiline and emetine) may have a therapeutic effect on neocoronary, but clinical trials are still needed to confirm their effects ( Mikhael et al, 2022 ; Zhang et al, 2022 ). In addition, many data show that diabetes is also a factor in causing severe symptoms of COVID-19 ( Zhou F. et al, 2020 ; Godeau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified a production error. Figure 8 was not correctly processed by the publisher.…”
mentioning
confidence: 99%